Psychometric validation of the Danish BREAST-Q reconstruction module - Cecilie Balslev Willert; Karl Bang Christensen; Pernille Envold Bidstrup; Lene Mellemkjær; Anne-Marie Axø Gerdes; Lisbet Rosenkrantz Hölmich (Breast)
Aim/background: Patient-reported outcome measurement instruments are important tools in understanding a breast reconstruction's impact on the patients' quality of life. A psychometric validation is essential before applying a patient-reported outcome measurement instrument in clinical practice and research. The BREAST-Q is a specific, validated questionnaire for breast surgery outcomes that has been translated from English to Danish. It consists of 167 items in 7 pre-operative scales and 15 post-operative scales. This validation study aims to validate the Danish BREAST-Q reconstruction module. Material and methods: Eligible women were included from January 2019 to June 2020. Multiple-item scales with summated scores and more than 40 complete responses were eligible for psychometric validation, and psychometric analyses examined reliability and validity using Rasch Analyses and Classical Test Theory. Measurements included test for local response dependence, item fit, differential item functioning, and more. Clinical validity was assessed using known-groups hypotheses. Results: We obtained 115 and 201 complete responses pre-and postoperatively, respectively. We validated 120 items in four preoperative and nine postoperative scales. The Rasch analyses disclosed evidence of local response dependence in eight scales. Chronbach's α ranged 0.81–0.95 after adjustment. Item fit was evaluated using item-restscore correlations and showed good fit in 98 % of items. Differential Item Functioning was found in four items but had very little effect on the model. Clinical validity was supported by the know-group analyses. Discussion/conclusion: The Danish BREAST-Q reconstruction module has good acceptability, feasibility and validity, and adequate reliability. The results support the use in a Danish population.